Transcriptomics reveal immune downregulation of newts overwhelmed by chytrid co‐infection. Issue 17 (26th August 2020) - Shepack, Alexander; Catenazzi, Alessandro
Abstract : What happens when two emergent diseases infect the same host? In a From the Cover article in this issue of Molecular Ecology, McDonald et al. (2020) compare transcriptomic responses to co‐infection by the two chytrid fungi in the skin, liver and spleen of Eastern newts ( Notophthalmus viridescens ). Novel molecular tools, such as high‐throughput DNA sequencing for genome discovery and transcriptomics, have revolutionized our understanding of host–pathogen interactions and disease ecology (Güimil et al. 2005; Rosenblum et al. 2012). For example, epidemiologists are using genomic data to track the spread of the emergent SARS‐CoV‐2 in real time, both locally and globally. RNA sequencing (RNA‐Seq) is routinely employed to study response to disease in humans, improving disease diagnostics, profiling and development of intervention strategies. Transcriptomic profiles may be particularly informative for emergent diseases, whose pathologies and effect on host phenotype are poorly known. Fungal pathogens increasingly threaten a variety of wild and domesticated organisms (Fisher et al. 2012), and two chytrid fungi attacking amphibians are causing one of the worst losses of vertebrate biodiversity ever recorded (Scheele et al. 2019).